Characterization of chlorogenic acids (CGA) and nine isomers in an F2 population derived from Coffea arabica L. (2019)
ABSTRACT Chlorogenic acids (CGA) and their isomers have been associated with sensory attributes of the coffee beverage such as acidity, astringency, and bitterness. They have been linked to coffee rust resistance and acknowledged as bioactive compounds due to their antioxidant power with benefits for human health. The total chlorogenic acids (TCGA) and nine isomers of three groups, caffeoylquinic acid or CQA (5-CQA, 4-CQA, 3-CQA), dicaffeoylquinic acid or diCQA (3,4-diCQA; 3,5-diCQA, 4,5-diCQA) and feruloylquinic acid or FQA (5-FQA, 4-FQA, 3-FQA) were determined in an F2 population of Coffea arabica from the crossbreed (Bourbon x Maragogype) x Timor Hybrid. TCGA contents were quantified by UV-VIS spectrophotometry and High-Resolution Liquid Chromatography - HPLC. The group of caffeoylquinic acids (CQA) represented 82% of the TCGA. From the diCQA, 4,5-diCQA showed lower contents, whereas the highest isomer was 3,5-diCQA. Results per quartile for TCGA-UV and for every isomer showed statistical differences among group averages per isomer. The population behaved as a parental Maragogype according to contents of 5-CQA, 3,5-diCQA, and TCGA-UV. TCGA contents were higher in the parental GQ956 derived from the Timor hybrid 832-1, with resistance to coffee rust. From the three groups, the first characteristic of parental Bourbon showed a higher concentration of diCQA and FQA; the second one showed a lower concentration of TCGA and CQA isomers and the third group higher TCGA and 5-CQA concentrations. This research allowed establishing the basis for plant selection in the F2 generation of C. arabica due to the TCGA content and isomers derived from CQA, diCQA, and FQA.